Hotspots of human mutation point to clonal expansions in spermatogonia - Vladimir Seplyarskiy; Mikhail A. Moldovan; Evan Koch; Prathitha Kar; Matthew D. C. Neville; Raheleh Rahbari; Shamil Sunyaev (Nature, 2025)
Abstract In renewing tissues, mutations conferring selective advantage may result in clonal expansions 1–4 . In contrast to somatic tissues, mutations driving clonal expansions in spermatogonia (CES) are also transmitted to the next generation. This results in an effective increase of de novo mutation rate for CES drivers 5–8 . CES was originally discovered through extreme recurrence of de novo mutations causing Apert syndrome 5 . Here, we develop a systematic approach to discover CES drivers as hotspots of human de novo mutation. Our analysis of 54,715 trios ascertained for rare conditions 9–13 , 6,065 control trios 12,14–19 and population variation from 807,162 mostly healthy individuals 20 identifies genes manifesting rates of de novo mutations inconsistent with plausible models of disease ascertainment. We propose 23 genes hypermutable at loss-of-function (LoF) sites as candidate CES drivers. An extra 17 genes feature hypermutable missense mutations at individual positions, suggesting CES acting through gain of function. CES increases the average mutation rate roughly 17-fold for LoF genes in both control trios and sperm and roughly 500-fold for pooled gain-of-function sites in sperm 21 . Positive selection in the male germline elevates the prevalence of genetic disorders and increases polymorphism levels, masking the effect of negative selection in human populations. Despite the excess of mutations in disease cohorts for 19 LoF CES driver candidates, only 9 show clear evidence of disease causality 22 , suggesting that CES may lead to false-positive disease associations.